2020
DOI: 10.1075/babel.00156.hav
|View full text |Cite
|
Sign up to set email alerts
|

Video-mediated remote interpreting in healthcare

Abstract: Interpreters face distinct challenges when deployed remotely via video link, due to their virtual presence but physical absence in the conversation. Depending on the interpreting service, interpreters can also be exposed to greater spontaneity and hence increased pressure if video-mediated interpreting is offered as an instant service. The examples discussed in this paper draw on an interpreting studies-based analysis of the Austrian pilot project “Vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Among them, Mouzourakis (2006) reviewed the large-scale DI experiments that were conducted at the United Nations and the European Union institutions in which the subjective data collected by questionnaire were used to indicate how the technical setup for sound and image transmission would impact interpreters’ perceptions of DI. Later, this method was also adopted in DI studies to evaluate interpreters’ stress levels ( Ko, 2006 ; Bower, 2015 ; Costa et al, 2020 ), the effect of interpreters’ visibility on participants ( Licoppe and Veyrier, 2017 ), turn-taking ( Davitti and Braun, 2020 ; Havelka, 2020 ), and the effect of different presentation modalities ( Braun, 2007 ).…”
Section: Measurement Methodsmentioning
confidence: 99%
“…Among them, Mouzourakis (2006) reviewed the large-scale DI experiments that were conducted at the United Nations and the European Union institutions in which the subjective data collected by questionnaire were used to indicate how the technical setup for sound and image transmission would impact interpreters’ perceptions of DI. Later, this method was also adopted in DI studies to evaluate interpreters’ stress levels ( Ko, 2006 ; Bower, 2015 ; Costa et al, 2020 ), the effect of interpreters’ visibility on participants ( Licoppe and Veyrier, 2017 ), turn-taking ( Davitti and Braun, 2020 ; Havelka, 2020 ), and the effect of different presentation modalities ( Braun, 2007 ).…”
Section: Measurement Methodsmentioning
confidence: 99%
“…Nonetheless, when VMI was used in a healthcare setting, the waiting time was not necessarily long. For example, Havelka [14] reported that in Austria interpreters for VMI service were required to be available within 120 seconds. Besides, the time it took users to schedule interpreting service (i.e., the period after one sends out a service request and before one successfully books the service) seemed to be shorter in VMI than on-site, since in VMI one did not have to waste time for rescheduling when no on-site interpreter was available in the initial desired time and/or place [15].…”
Section: Review Of Research Designs and Research Findingsmentioning
confidence: 99%
“…The last research topic of the recent VMI studies is interpreters' use of strategies in VMI, which is a topic that none of the three previous VMI reviews discussed. Seven out of the 27 studies selected for the current review explored interpreters' strategy use in VMI [2,4,6,14,22,24,25], of which the major findings are summarised below. The strategies identified by these studies could be roughly categorized into four types, that is, strategies for source language (SL) comprehension, strategies for note-taking, strategies for target language (TL) production, and strategies for turn management in VMI.…”
Section: Review Of Research Designs and Research Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current situation of a highly contagious COVID 19 pandemic, tele-conferencing and video-interpreting have been adopted as the preferred option to minimize face to face contact between individuals. For future research, we recommend wide-spread evaluation of videoconferencing (Korak, 2012;Braun, 2015b;Havelka, 2020) in SRH consultations in refugee settings.…”
Section: Telephone Versus On-site Interpreters In Srhmentioning
confidence: 99%